Weight optimization of leaf spring assembly using design for manufacturing approach and FEM in graduated leaves for Electric Vehicle - Mohammed Irfan Khan; Anil Patel; Shubham Soni; Chitresh Nayak (International Journal of Applied Mechanics and Engineering)
The aim of this study is to determine the ideal stress distribution for a multi-Leaf Spring assembly using finite element analysis. Furthermore, the topology enhanced model, based on associate load is included in this research work. This work is carried out by considering two different techniques involving design for manufacturing (DFM) after the attainment of results from topology optimization. The vehicle's overall load is bear by the main leaf spring and graduated leaves are used to support the main leaf thus the prospective techniques intend to create holes across the graduated leaves and cut a custom slot along the graduated leaves of the spring assembly. The disclosure manifest that it is feasible to lessen the leaf spring assembly weight in order to create a lightweight, structurally sound design and reduce energy consumption that can be employed to heavy-duty commercial electric vehicles. The suggested techniques promisingly anticipate that a significant proportion of weight deduction of about 3.4 percent with holes and 17.34 percent with slots can be attained in multi-leaf spring assembly.